Three-phase load balancing control system for low-voltage power distribution network - CHEN GE (2017)
The invention discloses a three-phase load balancing control system for a low-voltage power distribution network. The power load of a user side is divided into a low-power load part directly connected into the power distribution network and a high-power load part connected into the power distribution network through a phase commutation device. The total power load of each user side and a multi-preset-cycle power average value of a to-be-connected phase commutation device are acquired, the phase with the low total phase power load of the low-voltage power distribution network or the phase commutation device needing trial phase switching on the phase with the low total phase power load is determined through calculation, the phase of the phase commutation device tries to be switched, the to-be-connected phase commutation device tries to be connected into the phase with the low total phase power load, if the loads of the three phases meet the balance requirement, the phase of the phase commutation device is switc